O uso de placas fotovoltaicas: uma revisão bibliográfica - Costa, Raycam Evaristo de Oliveira (Universidade Federal Rural do Semi-Árido, 2020)
The production of electric energy by methods known as clean and renewable has grown every year and, among the existing generation methods, it is possible to observe a notable highlight for the production using photovoltaic plates. This study aims to analyze in the literature, issues pertinent to photovoltaic systems. Throughout the work, the reader will be presented with historical, physical and engineering aspects regarding the process of creating systems of this nature. Through a bibliographic search, the study pointed out some factors that influence the conversion of solar energy into electricity. In addition, the possible types of implementation of residential and industrial projects, the so-called On-grid and Off-grid, will be discussed. It was possible to observe that when thinking about implementing a project using solar panels, one should take into account climatic and geographic factors, in addition to technical characteristics related to the plates and that the On-grid system is more advantageous compared to the Off-grid in terms of regards the costs of the implementation process.
Monografia
Keywords: Energia solar; Energia fotovoltaica; Geração de energia; Fatores; Solar energy; Photovoltaics; Power generation; Factors; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA